What shapes M&A markets? Corporate and institutional drivers in the US and Germany - Carmen Giovanazzi (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
We analyze the dynamics of mergers and acquisitions (M&A) in the United States (US) and Germany in the 2000s, drawing on the Varieties of Capitalism (VoC) framework and the concept of internal capitalist diversity. Using SDC Platinum transaction data from 2000 to 2023 and qualitative insights from semi-structured interviews with 28 M&A professionals, we investigate how firm characteristics and institutional frameworks drive M&A activity in both countries. We confirm VoC-based expectations regarding transaction volumes and industry patterns but also highlight the professionalization of M&A functions across large, listed firms, alongside an increasing role of financial acquirers in both markets. While the rise of private equity aligns with the exit-driven strategies of small and medium-sized enterprises (SMEs) in the US, it raises questions regarding family-owned SMEs in Germany, which prioritize continuity and legacy but increasingly face succession challenges. Our findings suggest a continued hybridization of Germany's stakeholder-oriented corporate governance, integrating shareholder-oriented practices beyond large, listed firms.
Keywords: G34; L2; P52; 330; M&A; Varieties of Capitalism; Financialization; Germany; US